(untitled) (Malay Literature, 2024)
The exploration of figurative expressions aims to identify the conceptual frameworks in traditional Malay texts, specifically focusing on the Undang-Undang Melaka (Laws of Melaka) and the Undang-Undang Laut (Maritime Laws). These legal codes feature a variety of figurative expressions, such as idioms, similes, and metaphors, which serve to clarify legal principles, societal standards, and cultural values of the Malay people at that time. This study aims to examine how the use of figurative expressions contributes to understanding the development of intellectual frameworks of the Malay community. Interdisciplinary methodologies, including historical research and literary analysis are employed to provide a comprehensive view of how figurative expressions contribute to the exploration of intellectual frameworks in traditional Malay manuscripts. The use of figurative language to convey legal and societal norms reflects the intricate thought processes of the Malay community. These linguistic features reveal the Malay intellectual tradition, which intertwines legal, ethical, and cultural elements into a cohesive narrative, highlighting the importance of language in shaping and preserving cultural identity. Full text: PDF